The impact of political freedom on economic growth: An analysis using system estimation and linear dynamic panel estimation - Mercado, Mary Catherine A. (Animo Repository, 2023)
The question of whether political freedom promotes economic growth and development has policy implications for developing countries, given the cost of institutional change. While democracies tend to achieve higher growth, previous empirical research has not been conclusive on this question. This paper extends the literature by first constructing a dynamic linear panel model to identify the impact of political freedom on economic output while controlling for GDP dynamics. This approach is complemented by a system of equations model that relates political freedom to economic output through economic institutions and estimating its indirect impact using three-stage least squares (3SLS). The findings indicate that political freedom positively impacts economic institutions and economic output when measured as a stock of democratic experience, promoting long-run economic growth. These effects also vary when interacted with natural resource dependency and regional factors, with a statistically significant positive effect for resource-poor countries. Overall, democracy and political freedom do enhance growth when promoted alongside a development strategy that also builds key economic institutions such as property rights.